2003
DOI: 10.1097/01.ju.0000048686.50716.ef
|View full text |Cite
|
Sign up to set email alerts
|

Transvaginal Radio Frequency Treatment of the Endopelvic Fascia: A Prospective Evaluation for the Treatment of Genuine Stress Urinary Incontinence

Abstract: The transvaginal radio frequency applicator demonstrated good efficacy and excellent safety at 1-year followup. Ongoing analysis of the data has indicated opportunities for improvement of this new surgical technique that could result in higher efficacy rates without compromising safety. Further long-term evaluation is being conducted to assess chronic durability of the procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
1
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 16 publications
0
16
1
1
Order By: Relevance
“…This low and dropping effectiveness is lower than that reported in one of the two studies published to date [14] but concurs with the other [15]. It is notable that long-term results of the first study have not been published.…”
Section: Discussioncontrasting
confidence: 53%
See 2 more Smart Citations
“…This low and dropping effectiveness is lower than that reported in one of the two studies published to date [14] but concurs with the other [15]. It is notable that long-term results of the first study have not been published.…”
Section: Discussioncontrasting
confidence: 53%
“…A standard surgical technique was followed [14]. All procedures were done in theatre, under general or spinal anaesthesia.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…They also reported a high patient satisfaction rate of 81%. Dmochowski et al [4] applied radiofrequency transvaginally to 120 patients and reported this approach to be as effective and safe as laparoscopic application. No major intra-or postoperative complications were reported in any of these studies.…”
Section: Introductionmentioning
confidence: 99%
“…After promising clinical trial results, this system became available in 2002 and was used enthusiastically for several years. Short-term data from prospective, nonrandomized trials suggested significant improvement in stress urinary incontinence symptoms [5,6]. Longer-term data, however, were less favorable [7].…”
mentioning
confidence: 99%